DESTINATION BRAND EXPERIENCE IN TOURISM RESEARCH: A THEMATIC REVIEW AND FUTURE RESEARCH AGENDA - Jiao , Wei; Zainol, Zuraidah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Destination brand experience (DBE) has become a central construct in tourism marketing, capturing tourists’ sensory, emotional, cognitive, and behavioral responses to destination brands. Despite growing interest, no review has examined the conceptual development and empirical findings specific to DBE. This paper conducts a thematic review of 42 studies published between 1996 and 2025, synthesizing current knowledge across five themes: conceptualization and dimensional structure, theoretical foundations, antecedents, outcomes and consequences, and methodological approaches. The four-dimensional framework (sensory, affective, behavioral, intellectual) from Brakus et al. (2009) remains dominant, though relational and spiritual dimensions are gaining attention. The Stimulus-Organism-Response model and Social Exchange Theory are the most applied lenses, yet many studies lack explicit theoretical grounding. A clear gap exists between extensive outcome research and limits antecedent investigation. An integrative framework and seven-point future research agenda are proposed. This review provides the first dedicated synthesis of DBE research, offering guidance for scholars and destination marketers.